Tourism landscape: understanding the swiftlet “hotel” phenomenon - Awang, Khairil Wahidin; Hassan, Mazlan; Abdullah, Abdul Rashid (Penerbit Universiti Teknologi Malaysia, 2015)
The aim of this paper is to examine the effects of the swiftlet “hotels” to the tourism industry. Tourism is a big business in Malaysia, so is edible swiftlet’s nest. The medicinal values appropriate to the nests by mainly ethnic Chinese result in high demand for them. This creates a booming sector over the horizon, with swiftlet houses dotting the urban and rural landscapes of the country. This study utilized a qualitative approach, with semi-structured in-depth interviews and personal observation employed on swiftlet houses and their owner-operators. Preliminary results suggest bigger swiftlet house operators possessed the notion of expanding their businesses by offering a variety of swiftlet nest-related products and by showcasing the processes to end users. Such action ensures a spillover effect to the tourism industry. On the other hand, findings also suggest that the rise of many of these swiftlet houses in place of conventional types of businesses in urban area has relatively tampered with the authenticity of the built environment.